Menguatkan Niat Berwirausaha : Analisis Moderasi Efikasi Diri pada Pendidikan Kewirausahaan dan Kreativitas - Hidayat, Rahmad Wahyu (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
Indonesia has the advantage of a demographic bonus. Demographic bonus can have a negative impact if not managed properly. One of them is unemployment. Jobs not proportional to the number of workers are the leading cause of unemployment. Entrepreneurship is a solution to increase employment. This study aimed to determine the effect of entrepreneurship education and creativity on entrepreneurial intentions, with the moderating variable of self-efficacy. This study uses quantitative methods with a sample of 55 students. The data obtained were tested using multiple linear regression and moderated regression analysis. The findings of this study indicate that entrepreneurship education and creativity have a significant influence on entrepreneurial intentions. Then, self-efficacy can moderate the effect of entrepreneurship education and creativity on entrepreneurial intentions.